Optimizing interfacial interactions between functionalized graphene and chitosan for enhanced strength and toughness of composite films - Tengxin Zhang; Han Wang; Yabin Hao; Chang Liu; Yan Zhao; You Zeng (eXPRESS Polymer Letters)
Remarkable mechanical reinforcement of chitosan films using graphene is extremely important to greatly widen the practical application of chitosan (CS) in many fields, but there still exist challenges to regulating graphene-CS interactions for both enhanced strength and toughness. In this work, we functionalized graphene oxide (GO) with carboxyl (G-COOH) and amino groups (G-NH2), and investigated the effects of interfacial interactions on the mechanical properties of graphene/CS composite films in detail. We found that the G-NH2/CS composites exhibited the most remarkable reinforcement in both tensile strength and toughness than the GO/CS and G-COOH/CS composites, even different from a theoretical prediction on graphene-CS interactions. Such remarkable reinforcement is mainly attributed to the moderate graphene-CS interaction, uniform dispersion, and high alignment of G-NH2 in CS films.